2010
DOI: 10.1007/s10096-010-1075-z
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal bacterial colonization during the first wheezing episode is associated with longer duration of hospitalization and higher risk of relapse in young children

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 42 publications
2
20
3
1
Order By: Relevance
“…Lower airway colonization with these organisms was also associated with higher blood eosinophil counts and total IgE levels, but not specific IgE levels, at 4 years and with bronchodilator reversibility and development of asthma at 5 years. In a study of children under 3 years hospitalized for viral-induced wheezing, 60% demonstrated nasopharyngeal (NP) colonization with Streptococcus pneumoniae , Moraxella catarrhalis , or Haemophilus influenzae , and this was associated with increased risk of recurrent wheezing episodes during the following year 14 . Importantly, antibiotic use may select for these organisms 12 .…”
Section: Microbial Exposurementioning
confidence: 99%
“…Lower airway colonization with these organisms was also associated with higher blood eosinophil counts and total IgE levels, but not specific IgE levels, at 4 years and with bronchodilator reversibility and development of asthma at 5 years. In a study of children under 3 years hospitalized for viral-induced wheezing, 60% demonstrated nasopharyngeal (NP) colonization with Streptococcus pneumoniae , Moraxella catarrhalis , or Haemophilus influenzae , and this was associated with increased risk of recurrent wheezing episodes during the following year 14 . Importantly, antibiotic use may select for these organisms 12 .…”
Section: Microbial Exposurementioning
confidence: 99%
“…A post-hoc analysis in a cohort of children younger than 3 years of age hospitalized for their first viral induced wheezing episode (viral swab positive in 93% of participants) showed that 60% of these children had positive NP culture for Streptococcus pneumoniae, Haemophilus influenzae , or Moraxella catarrhalis . In addition, children with bacterial colonization of the upper airway had longer durations of hospitalization and were more likely to develop recurrent wheezing in the year following the initial wheezing compared to children without evidence for bacterial colonization 33 .…”
Section: Airway Bacterial Colonization and Exacerbation Of Early Chilmentioning
confidence: 99%
“…In addition, we were not able to demonstrate any synergy between viral infections and PNC colonization, or, more specifically, between RSV infection and PNC colonization, in relation to later outcome. In a previous Finnish study, nasopharyngeal bacterial colonization, documented on positive cultures for S. pneumoniae , H. influenzae and M. catarrhalis , during the first wheezing episode in children younger than 3 years of age was associated with a longer duration of hospitalization and higher risk of relapses of wheezing within 2 months after hospitalization . In addition, a recent study demonstrated the capability of S. pneumoniae to contribute to the severity of respiratory tract illnesses during rhinovirus infection, including asthma exacerbations .…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies on PNC colonization during wheezing in children have suggested that S. pneumoniae may not be an innocent bystander during the respiratory infection . The aim of the present study was therefore to evaluate whether PNC colonization during the first wheezing episode in early childhood is a determinant of subsequent wheezing or later asthma, atopy and lung function in childhood, adolescence or adulthood.…”
mentioning
confidence: 93%
See 1 more Smart Citation